2005
DOI: 10.4049/jimmunol.174.10.5921
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Acquisition of TLR Tolerance during Malaria Infection Impacts T Cell Activation

Abstract: An effective immune response to infection requires control of pathogen growth while minimizing inflammation-associated pathology. During malaria infection, this balance is particularly important. Murine malaria is characterized by early production of proinflammatory cytokines, which declines in the face of continuing parasitemia. The mechanism by which this occurs remains poorly understood. In this study, we investigated the role of dendritic cells (DCs) in regulating pro- and anti-inflammatory cytokine respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
96
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 30 publications
(28 reference statements)
13
96
0
1
Order By: Relevance
“…Moreover, although T-cell hyporesponsiveness was observed during infection, it occurred to the same extent in PyL and PyNL infections and seemed to result from failure of CD11b ϩ APCs from infected animals to drive IL-2-dependent T-cell proliferation. These results are in agreement with previous studies with P. yoelii (26,37) in which it was suggested that T-cell hyporesponsiveness during malaria infection was due to the acquisition of Toll-like receptor tolerance (26,37) and mediated, by a soluble mediator that is not nitric oxide, prostaglandin E2, or TGF-␤ (26). We have confirmed that this downmodulation of T-cell activation is not mediated by TGF-␤ alone (data not shown), but we cannot yet rule out the possibility that TGF-␤ might act in combination with other regulatory molecules.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, although T-cell hyporesponsiveness was observed during infection, it occurred to the same extent in PyL and PyNL infections and seemed to result from failure of CD11b ϩ APCs from infected animals to drive IL-2-dependent T-cell proliferation. These results are in agreement with previous studies with P. yoelii (26,37) in which it was suggested that T-cell hyporesponsiveness during malaria infection was due to the acquisition of Toll-like receptor tolerance (26,37) and mediated, by a soluble mediator that is not nitric oxide, prostaglandin E2, or TGF-␤ (26). We have confirmed that this downmodulation of T-cell activation is not mediated by TGF-␤ alone (data not shown), but we cannot yet rule out the possibility that TGF-␤ might act in combination with other regulatory molecules.…”
Section: Discussionsupporting
confidence: 83%
“…IL-10 production by APCs themselves appears to be minimal in this situation. These data thus both confirm and significantly extend observations from the P. yoelii, P. chabaudi, and P. berghei infection models in which the primary defect appears to be at the level of the APC (26,29,37,53). Clearly, by 7 days p.i., splenic CD4 ϩ T cells from P. yoelii-infected mice have lost their ability to make and respond to IL-2 by proliferation, but they have enhanced capacity for production of both IFN-␥ and IL-10, and both of these cytokines are more abundantly produced by T cells from PyL-infected mice than by T cells from PyNLinfected mice.…”
Section: P Yoelii-induced T-cell Hyporesponsiveness Is Both Cd11bsupporting
confidence: 78%
See 1 more Smart Citation
“…Among a variety of immune evasion mechanisms, DCs, which play central roles in establishing immunity, are the major target for malaria parasites. For instance, malaria parasites interfere with the maturation of DCs (3,36,37) or prevent Ag cross-presentation (38), both of which result in the failure to directly activate protective/effector T cells. Unlike these observations, our findings propose a novel interaction of malaria parasites with DCs via TLR9 that affects Tregs rather than protective T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of repeated high-dose stimulation of TLR7 to human disease is unclear. Repeated administration of TLR9 agonist disrupts lymph node and splenic architecture [42] and repeated dosing in a rapid schedule induces TLR signalling tolerance [43]. Either mechanism may explain disease inhibition following repeated exposure to high doses of TLR7/8 or TLR9 agonists.…”
Section: Tlr7/9 Agonists Activate Nod-derived Bmdcs and Cause The Secmentioning
confidence: 99%